2018
DOI: 10.1159/000488484
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties and Factor Analysis of the Engagement and Independence in Dementia Questionnaire (EID-Q)

Abstract: Background/Aims: Independence and social engagement are important outcomes for people with dementia. The aim of this study was to conduct an in-depth psychometric assessment of the Engagement and Independence in Dementia Questionnaire (EID-Q), a measure of social independence. Methods: This was an observational study at five NHS sites across England. Participants completed the EID-Q alongside additional measures. Psychometric analysis included internal consistency, test-retest reliability, convergent validity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Thirty-five self-report instruments (of which one instrument has two independently developed sub-scales 1 ) used in dementia research were identified and allocated to respective conceptual domains (Table 2 ). For example, the Gratitude Questionnaire [ 93 ] was categorised within ‘Social Well-being: Connection and Belonging’, since gratitude is seen as a social construct [ 113 ], whilst the Engagement and Independence in Dementia Questionnaire - EID-Q [ 77 ] -, contained just one item for participation in hobbies, and none on social engagement, so this instrument was allocated to ‘Psychological Well-Being: Agency and Purpose’.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-five self-report instruments (of which one instrument has two independently developed sub-scales 1 ) used in dementia research were identified and allocated to respective conceptual domains (Table 2 ). For example, the Gratitude Questionnaire [ 93 ] was categorised within ‘Social Well-being: Connection and Belonging’, since gratitude is seen as a social construct [ 113 ], whilst the Engagement and Independence in Dementia Questionnaire - EID-Q [ 77 ] -, contained just one item for participation in hobbies, and none on social engagement, so this instrument was allocated to ‘Psychological Well-Being: Agency and Purpose’.…”
Section: Resultsmentioning
confidence: 99%
“…Dementia- specific measure of perceived involvement in everyday decision-making - some psychometric properties reported. Engagement and Independence in Dementia Questionnaire (26-item EDI-Q) b [ 77 ]. Dementia specific measure – some psychometric properties reported by scale developers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…People with dementia can face unique challenges and difficulties, however, there can still be a misconception that they lack the capacity for positive engagement or growth (Graham et al, 2003). Our recent body of research, during which we developed positive psychology outcome measures for older adults with mild dementia, suggests that they are equally capable of experiencing and articulating often complex concepts such as resilience (Stoner, Orrell, & Spector, 2018a) and social engagement (Stoner, Orrell, & Spector, 2018b), as described by Gough et al, (2018). Although knowledge transfer interventions may be challenging for people with dementia, due to the nature of the condition, this should not automatically exclude them and people with milder cognitive impairment could be supported to take part.…”
mentioning
confidence: 99%
“…People with dementia can face unique challenges and difficulties; however, there can still be a misconception that they lack the capacity for positive engagement or growth (Graham et al ., 2003). Our recent body of research, during which we developed positive psychology outcome measures for older adults with mild dementia, suggests that they are equally capable of experiencing and articulating often complex concepts such as resilience (Stoner et al , 2018a) and social engagement (Stoner et al , 2018b), as described by Gough et al . (2018).…”
mentioning
confidence: 99%